2014
DOI: 10.1155/2014/532953
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alendronate on Proteome of Hepatocellular Carcinoma Cell Lines

Abstract: Cancer is a life threatening disorder effecting 11 million people worldwide annually. Among various types of cancers, Hepatocellular carcinoma (HCC) has a higher rate of mortality and is the fifth leading cause of cancer related deaths around the world. Many chemotherapeutic drugs have been used for the treatment of HCC with many side effects. These drugs are inhibitors of different cell regulatory pathways. Mevalonate (MVA) pathway is an important cellular cascade vital for cell growth. A variety of inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Many chemotherapeutic drugs have been used for the treatment of HCC and it has own implicated therapeutic effect. Alendronate is pyrophosphate analogues which, one of the potential anticancer drug [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many chemotherapeutic drugs have been used for the treatment of HCC and it has own implicated therapeutic effect. Alendronate is pyrophosphate analogues which, one of the potential anticancer drug [17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides MVA pathway inhibitor, bisphosphonates (BPs)have inhibitory bone resorption property and studies also suggested there anticancer activity in various cancer including breast cancer [16,17]. BPs exert their effects through inhibition of bone resorption and bone-derived growth factors that ultimately results in inhibition of tumor cell invasion [18], proliferation [19] and increased apoptosis [20] [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…supplemented with 10% fetal bovine serum (Sigma) and 100 μg/mL of penicillin and streptomycin (Life technologies Inc.) in a free gas exchange with atmospheric air at 37 0 C.Drug TreatmentCells were in exponential growth phase, subjected for drug treatment. The concentration of alendronate was calculated on the basis of previous studies[14,15]. Cells were treated with 5µM, 10 µM, 20 µM Alendronate (ALN).…”
mentioning
confidence: 99%
“…after treatment with ALD has also been observed [27]. ALD inhibited the proliferation of the Huh-7 hepatocellular carcinoma cell lines in a time and dose dependant manner at concentrations between 5-20 μM [28]. ALD has also been shown to have anti-proliferative effect on the epidermoid carcinoma cell line A431, as well as inhibiting cell invasion in a matrigel invasion assay [29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%